Effects of Different Estrous Synchronization Methods on the Composition of Simmental Cow's Milk - Seker, Ibrahim; Risvanli, Ali; Calicioglu, Mehmet; Incili, Gokhan Kursad; Saat, Nevzat (Univ Fed Rio Grande Do Sul, 2017)
Background: Estrous synchronization is one of the primary applications performed to improve the fertility and to consolidate the parturition times in dairy cattle farms. Since the primary objective is to increase fertility regardless of the method of synchronization used, the effect of this process on the udder health and the quality of milk is generally ignored. Therefore, in the present study, the aim was to investigate the effect of different estrous synchronization methods t on the milk quality in a dairy cattle farm. Materials, Methods & Results: In this study, a total of 100 Simmental cows the same farm under good management practices were used. The animals were randomly divided into 4 groups of 25 cows each. The animals in the 1st group were used as a control group without any treatment. Progesterone-releasing intravaginal device (PRID) was inserted to the animals in the 2nd group, double dose of prostaglandin F-2 alpha (PGF(2)-alpha) with 11 days apart was applied to the animals in the 3rd group, and the Ovsynch protocol was applied to the animals in the 4th group. Starting from the first day of the applications, milk samples from each milk tank belonging to the groups were taken, kept frozen for 3 months and analyzed for the levels of fat, nonfat solids, density, protein, lactose and minerals over the course of one month. According to the results, the minimum milk fat content was found in the PRID group as 2.47 +/- 0.354%, and the highest value was in the PGF(2)-alpha group as 3.58 +/- 0.207%. The difference in milk fat ratio between the groups was found to be significant (P < .05). However, the differences between the groups for other parameters were not significant (P > .05). Discussion: Among the reasons for the low values of the milk fat rates obtained in the present study than the mean values of all lactation milk fat rates of the Simmental breed, the effect of the lactation period in which the milk samples were collected comes to mind. Because, as we know, the first 45-60 day period following the start of lactation after parturition in cattle is accepted as the period in which daily milk yield reaches to the maximum level of the lactation period. This period lasts for a certain period of time, and then starts to decrease gradually. Among the non-hereditary factors, the most important factor causing changes in the composition of the milk and its amount is the lactation period. In this study, the significant difference in the milk fat rates between the control and the application groups is quite remarkable compared to the low level of milk fat rates in the milk in all groups. According to the multiple comparison test results to determine which groups these differences arise from, the difference was found to be particularly between the PGF(2)-alpha group and PRID group. In this study, no significant effects of different synchronization methods on all components of the milk except the milk fat and the density values were determined. But results indicate that Ovsynch group was the synchronization group that caused the minimum change in milk fat compared to the other groups.
Keywords: estrous synchronization; composition of milk; Simmental